Possible Effects of Synaptic Imbalances on Oligodendrocyte–Axonic Interactions in Schizophrenia: A Hypothetical Model - Mitterauer, Bernhard J.; Kofler-Westergren, Birgitta (Frontiers in Psychiatry, 2011)
Abstract A model of glial-neuronal interactions is proposed that could be explanatory for the demyelination identified in brains with schizophrenia. According to this model, receptors on astrocytes in glial-neuronal synaptic units are not functional, loosing their modulatory influence on synaptic neurotransmission. Hence, an unconstrained neurotransmission flux occurs that hyperactivates the axon and floods the cognate receptors of neurotransmitters on oligodendrocytes. The excess of neurotransmitters may have a toxic effect on oligodendrocytes and myelin, causing demyelination. In parallel, an increasing impairment of axons may disconnect neuronal networks. It is formally shown how oligodendrocytes normally categorize axonic information processing via their processes. Demyelination decomposes the oligodendrocyte-axonic system making it incapable to generate categories of information. This incoherence may be responsible for symptoms of disorganization in schizophrenia, such as thought disorder, inappropriate affect and incommunicable motor behavior. In parallel, the loss of oligodendrocytes affects gap junctions in the panglial syncytium, presumably responsible for memory impairment in schizophrenia.